The Irish constitutional tradition responsible government and modern Ireland, 1782 - 1992 - Ward, Alan J. 1937- (Catholic Univ. of America Press, 1994)
Combining constitutional theory, political history, and political science, Alan J. Ward's study provides an interpretation of the many attempts to solve Ireland's political problems by constitutional means. The broad time frame enables the author to examine Irish constitutionalism as a tradition and place it in the context of the political history of the British commonwealth, from which it derives